Community Behavior towards Plastic Waste: Case Study in Nagari Batu Basa as a Traditional Village - Haq, Syaiful; Hidayat, Hendra; Yuvenda, Dori (CIVED, 2024)
Sumatra Barat is a halal tourist area but many people throw rubbish carelessly. This phenomenon is a big problem, because environmental issues and waste are world issues. This study reveals the causes of people's behavior of littering using quantitative and qualitative methods. Using 30 observers who monitored community activities for 10 days. The population of this research is the people of Nagari Batu Basa, Pariangan Tanah Datar, Sumatra Barat, consisting of three Jorong (hamlet), Jorong Batu Basa, Jorong Koto Baru, and Jorong Sialahan. The results of the study reveal that people's behavior is to throw rubbish into the river because there are no regulations from the government, there are no rubbish bins, and there is no community initiative to make rubbish bins. People throwing rubbish carelessly has become a habit. People do not care about plastic waste because they do not have knowledge and understanding about plastic waste. Education about waste is also not provided to school students. Apart from that, the government does not pay special attention to plastic waste. The results of this study prove that regulations have an important role in shaping people's behavior in managing waste, especially plastic waste.